Mining automation: threat or opportunity for FDI technology spillovers? - Nahom Ghebrihiwet (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
The process of mining automation has accelerated in recent years. As a result, fewer workers are needed at mine-sites, and mining companies need high-technology equipment. This Perspective addresses how resource-rich countries need to adjust traditional local content regulation in order to foster FDI technology spillovers in the future.
Keywords: 330